The association between researchers’ conceptions of research and their strategic research agendas - Santos, J. M. (2021)
In studies of the research process, the association between how researchers conceptualize research and their strategic research agendas has been largely overlooked. This study aims to address this gap. This study analyzes this relationship using a dataset of more than 8,500 researchers across all scientific fields and the globe. It studies the associations between the dimensions of two inventories: the Conceptions of Research Inventory (CoRI) and the Multi-Dimensional Research Agenda Inventory - Revised (MDRAI-R). The findings show a relatively strong association between researchers' conceptions of research and their research agendas. While all conceptions of research are positively related to scientific ambition, the findings are mixed regarding how the dimensions of the two inventories relate to one another, which is significant for those seeking to understand the knowledge production process better. The study relies on self-reported data, which always carries a risk of response bias. The findings provide a greater understanding of the inner workings of knowledge processes and indicate that the two inventories, whether used individually or in combination, may provide complementary analytical perspectives to research performance indicators. They may thus offer important insights for managers of research environments regarding how to assess the research culture, beliefs, and conceptualizations of individual researchers and research teams when designing strategies to promote specific institutional research focuses and strategies. To the best of the authors' knowledge, this is the first study to associate research agendas and conceptions of research. It is based on a large sample of researchers working worldwide and in all fields of knowledge, which ensures that the findings have a reasonable degree of generalizability to the global population of researchers.